Clinical observation of sacubitril valsartan sodium in the treatment of resistant hypertension: A randomized clinical trial - Lyu, Tian-Jiao; Liu, Ying; Zhang, Hong; Li, Ling-Yan; He, Rui-Qing; Gao, Jun-Qing; Liu, Zong-Jun (Frontiers in Cardiovascular Medicine, 2022)
Objective To investigate the effectiveness and safety of sacubitril valsartan sodium in the treatment of resistant hypertension (RH). Methods This study is a single-center, prospective, randomized controlled study. According to the inclusion and exclusion criteria, patients with RH who met the criteria were screened, and all patients adjusted their drug treatment (valsartan 80 mg, amlodipine 5 mg, and hydrochlorothiazide 12.5 mg). After 4 weeks of drug elution, the random envelope method was used for random grouping. The treatment group took sacubitril valsartan sodium 200 mg, amlodipine 5 mg, hydrochlorothiazide 12.5 mg, and the control group took valsartan 80 mg, amlodipine 5 mg, and hydrochlorothiazide 12.5 mg for 8 weeks. The 24 h ambulatory blood pressure (BP) and the echocardiography index using the office sphygmomanometer were observed in the patients. Results A total of 100 patients with RH were included in the two groups, with 50 cases in each group. There were no significant differences in sex, age, or comorbid diseases between the two groups. During the 8-week follow-up, the office BP of the research group were significantly decreased (24.78/17.86 mmHg) compared with those of the control group. In the research group the 24 h average BP, daytime average BP, and nighttime average BP were 144.84/79.82, 147.10/82.06, and 138.67/76.31 mmHg at baseline, and reduced to 128.96/73.32, 131.50/74.94, and 122.11/69.27 mmHg at week 8, which were significantly decreased (P < 0.05 or P < 0.01), and the left ventricular ejection fraction was significantly increased (P < 0.05), compared with the control group. Conclusion Sacubitril valsartan sodium can effectively reduce BP and improve cardiac function in RH.